Design and Fabricate of 3D Printed X-Band Sample Size Based Polyethylene Terephthalate Glycol (PETG) Rectangular Waveguide - Mod Arsad, Nur Nazifa; Abdul Kadir, Herdawatie; Esa, Fahmiruddin; A. Majid, Huda; Che Alias, Muhammad Zulfauzan Fahmi; Mohd Ibrahim, Iffan Darwis; Ksm Kader Ibrahim, Babul Salam (International Journal of Integrated Engineering, 2025)
This work discusses the design and fabrication of 3D-printed dielectric materials for rectangular waveguides, with specific attention given to the effects of infill density and pattern changes on dielectric attributes. Microwave CST Studio is used to design the waveguide structures, which were produced through additive manufacturing and later tested with a two-port rectangular waveguide measurement system. The S-parameters were measured using a Keysight PNA-L Network Analyzer N5234B, whereby the reflection coefficient (S11) and the transmission coefficient (S21) were measured to determine how the material interacts with electromagnetic waves. It was found that greater infill densities correlated with increased values of real permittivity, whereas infill patterns have an essential influence on the material's dielectric behavior. Several patterns were tested: concentric, cross, cubic, and zigzag; the zigzag pattern gave the best results concerning the effective permittivity, while the concentric pattern presented the least because of the greater air gaps. The strong dependence of permittivity on infill density illustrates the possibility of controlling dielectric properties through additive manufacturing using PETG material. It has been demonstrated that 3D printing methods can fabricate waveguides and RF circuits that enable control over dielectric properties.